27.9k views
4 votes
Please help me Im lost on this :(​

Please help me Im lost on this :(​-example-1
User Dan Udey
by
4.9k points

2 Answers

3 votes

Answer: C) 3x^2+8x-10=-8

Explanation:

3x^2+8x-10x=-8

3x^2+8x-2=0

a=3 b=8 c=-2

Plug it into quadratic formula.

User Lahiru Dilshan
by
5.2k points
6 votes

Answer:

C

Explanation:

the quadratic formula is


\frac{ - b + \sqrt{b ^(2) - 4ac} }{2a}

Make the quadratic equal to 0, so it will be 3x^2 + 8x -2=0. Then substitute the values into the equation.

User PPTim
by
4.5k points